Workshops on mapping in Africa - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
The regional programs recently embarked on an impact pathway process for the sites where we work, kicked off by several workshops in East Africa, West Africa and, coming up, South Asia. Our overall objective was to strengthen the network of partners working on issues of climate change and food security and ensure progress towards our common vision of reduced poverty and hunger, improved human health and nutrition, and enhanced ecosystem resilience.